Geomorphological processes in channel heads initiated by groundwater outflows (The Parsęta catchment, north-western Poland) - Mazurek, Małgorzata (Quaestiones Geographicae, 2011)
Channel initiation is caused by a combination of various hydrogeomorphic processes. In the humid temperate zone of the Polish Plain, in areas with permeable deposits, seepage erosion is the primary mechanism of stream channel initiation. In the 24 channel heads selected in the southern part of the Parsęta catchment (NW Poland), the zones of occurrence of the following processes were identified: (1) seepage erosion; (2) falls, dry ravel events and slides; (3) creep, solifluction, surface runoff and erosion; (4) channel processes; and (5) landforms created under the impact of plants and animals. The co-occurrence of various morphogenetic processes produces variations in the accumulation conditions, and as a result, a diversity of deposits. Channel heads morphology shows the effect of the topography of the zero-discharge catchment, the type and magnitude of groundwater outflows, the variability of the geological structure, and the possibility of material being removed from the alcoves.